MINAT MEMBACA BUKU CERITA SISWA KELAS V MADRASAH IBTIDAIYAH MUHAMMADIYAH SUKAJATI HAURGEULIS - Siti Komariyah; Abdur Rahim (Bajang Institute, 2022)
Reading is one of the skills that must be possessed by a student. Students who like to read will have broader knowledge than students who do not like to read. One of the reading materials at school and at home is a story book. The problem faced by teachers in learning to read is the provision of media to raise awareness and concern for students to be interested in reading. Therefore, researchers are encouraged to conduct research on the interest in reading storybooks based on education. The purpose of this study was to determine the interest in reading story books, the motivating factors, and the efforts made to increase the interest in reading story books for the fifthgrade students of Madrasah Ibtidaiyah Sukajati Haurgeulis Indramayu. This type of research uses a qualitative descriptive research approach. To answer these problems, researchers used a qualitative approach. Data collection was carried out by means of interviews, observations, and documentation. The data obtained were analyzed by means of data reduction, data display, verification and conclusion. The results of this study indicate: (1) The reading interest of the fifthgrade students of Madrasah Ibtidaiyah Muhammadiyah Sukajati Haurgeulis Indramayu is in quite good condition. This is evident from the discussion which states that students have the ability to have an interest in reading and are very enthusiastic in participating in every learning activity in class. In addition, the reading interest of grade 5 A students depends on the methods and textbooks delivered by the teacher in delivering learning in class. (2) Factors that encourage students' interest in reading are family, talent, gender, education level, health condition, student habits, interesting reading books, and prizes. (3) Efforts made to increase students' interest in reading include adding book collections, holding competencies, and others.